Human Rights and Structural Adjustment - Abouharb, M. Rodwan (Cambridge University Press, 2013)
In 1981, theReagan administration in theUS, theThatcher administration in the UK, and their allies compelled the International Monetary Fund (IMF) and World Bank Group (known as the “International Financial Institutions” [IFIs]) to launch an ideological assault against the state and promote a shift in power from the state to the market.1 From 1981 to the present, the IFIs havefinanced structural adjustment agreements (SAAs) in developing and transition countries to achieve that goal.2 Structural adjustment agreements call upon recipient governments to liberalize and privatize economies in the context of strict budget discipline. Adjustment lending facilitates economic integration – the hallmark of globalization – on terms that are advantageous to corporate and finance capital